Total suspended solid variation during high/low tide of spring tide along Sampadi river, Sarawak - Bimol, Mordi; Lee, Nyanti; Ling, Teck Yee; Ismail, Norhadi; Emang, Justin Jok Jau (2009)
Total Suspended Solid (fSS) is important as one of the parameters that can be influenced by a stream power which will affect the ecological condition of the system. Therefore, the objectives of this study were to improve understanding in TSS variation along Sampadi River and provide fundamental data for monitoring purposes as Sampadi River is important for fisheries activities among the local people. Six sampling trips for samples collection were conductecl at 12 selected stations along 5ampadi River during high (February 25; October 22; and November 11) and low (February 25; May 21; and November 11) tide of Spring tide. Water samples for TSS analysis were collected in triplicates from the subsurface. Transparency and turbidity data were recorded in-situ. '5S values along Sampadi River during the study period ranged from 26.33±3.511!lgl·1 at station 1 to .04.33±7.57 mgt· 1 at station 13 during low tide. The range increased during high tide from 27.oo±13.89 mgl-1 at station 10 in February to 160.00±1.15 at station 12 in November. TSS at station 13 is significandy higher compared to all other stations during low tide. However during high tide, the TSS value at Station 12 is significandy higher compared to all stations but do not have significant difference as compared to station 13. Turbidity values range from 2.77±0.06 NTU at station 3 in May to 92.6±0.00 NTU at station 13 in February. However the range of values decreases slighdy during high tide, from 2.03±0.06 NTU at station 6 in October to 52.03±3.63 NTU at station 12 in November. Transparency, measured in centimeter ranged from 15.33±0.58 em at station 13 in February to 119.33±1.15 em at station 3 in November. While during high tide the transparency value increased to 28.67±1.15 em to 150.33±0.58 at station 3 in October during high tide. This suggests that TSS variation along Sampadi River support the theory of turbidity maximum zone which normally occurred at up or down estuary. Based on TSS values as compared to the Interim National Water Quality Index (INWQS) for Malaysia of the Department of Environment, Sampadi River falls into class III which is within range for common, ofeconomic value and tolerant species.